Діяльність українського культурно-освітнього товариства «Просвіта» на території Поліського воєводства у 1920-1930-і рр. - Крамар, Юрій Вікторович; Kramar, Yuriy V. (Східноєвропейський національний університет ім. Лесі Українки, 2014)
У статті висвітлюється культурно-освітня діяльність товариства «Просвіта» на території Поліського воєводства у 1920-1930-х рр. Показано, що «Просвіта» стала одним з головних осередків українського національно-культурного руху на Берестейщині у міжвоєнний період. Висвітлено характер взаємин польської адміністрації з місцевою українською громадою.This article studies the cultural and educational activity of the society Prosvita on the territory of the Polissia region in 1920-1930-s. We show that Prosvita became one of the main centers of ukrainian national and cultural mouvement in Brest region and that it created a wide network of its centers in Polissia during the interwar period. The society took care of the ukrainian schooling and it had developed different forms of out-of-school education among local Ukrainians. It also directed the school named after Oleksa Storozhenko in Brest, the only Ukrainian-language school in Polissia. Another aspect of this research is the character of the relation between Polish administration and local Ukrainian community. We come to a conclusion that the main goal of the Poland's state policy concerning Ukrainian population in Polissia was a complete elimination of any organizational forms of Ukrainian cultural and educational life in the region and a gradual denationalization of the Ukrainians.
The activity of the Ukrainian Cultural and Educational Society "Prosvita" in the Polissia region in 1920-1930-s.
Keywords: Поліське воєводство; товариство; шкільна освіта; національний рух; польська адміністрація; Polissia region; society; school education; national mouvement; Polish administration